2016
DOI: 10.1016/j.cyto.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytokine induction by TLR-activating vaccine adjuvants in human blood varies by age and adjuvant

Abstract: Most infections occur in early life, prompting development of novel adjuvanted vaccines to protect newborns and infants. Several Toll-like receptor (TLR) agonists (TLRAs) are components of licensed vaccine formulations or are in development as candidate adjuvants. However, the type and magnitude of immune responses to TLRAs may vary with the TLR activated as well as age and geographic location. Most notably, in newborns, as compared to adults, the immune response to TLRAs is polarized with lower Th1 cytokine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 72 publications
2
37
1
Order By: Relevance
“…For example, nucleotide-binding oligomerization domain (NOD)-like receptor-mediated IL-1β production is greater in human newborn cord than adult peripheral blood (43, 44) and slowly decreases to adult levels over the first years of life (45). A similar phenomenon for basal PGE 2 levels in WB has been observed (32). Therefore, further study of the IL-1β/PGE 2 axis as a predictive marker of vaccine reactogenicity may need to take ontogeny into account.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For example, nucleotide-binding oligomerization domain (NOD)-like receptor-mediated IL-1β production is greater in human newborn cord than adult peripheral blood (43, 44) and slowly decreases to adult levels over the first years of life (45). A similar phenomenon for basal PGE 2 levels in WB has been observed (32). Therefore, further study of the IL-1β/PGE 2 axis as a predictive marker of vaccine reactogenicity may need to take ontogeny into account.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously demonstrated that several of these licensed vaccines, such as the EasyFive (DTwP-HepB-Hib), induce distinct reactogenicity biomarker profiles in vitro (31, 32). When tested at equivalent v/v treatment concentrations, Δ lpxLI nOMV conversely induced a lower cytokine response for most innate cytokines (Figures 4A,B) and chemokines (Figure S7 in Supplementary Material) tested, grouping closer to pediatric vaccines such as PCV13 and HBV, than the more inflammatory (Alum + TLR agonist)-containing pediatric vaccines (i.e., PedvaxHIB and EasyFive).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with published data evaluating DCs and other APC in cord blood and from other neonatal murine models suggesting that more robust responses can predominate if distinct or multiple TLR agonists are engaged (53, 54). Further research is necessary to understand the checkpoints that must be met through TLR activation to both recruit cDCs into peripheral tissues and further induce their expression of co-stimulatory molecules as our data and that of others suggests that these signaling pathways are not comparably activated between adults and neonates (55). …”
Section: Discussionmentioning
confidence: 85%
“…As such, TLR2 could serve as a target for therapeutic treatment of allergic asthma [13][14][15]. Moreover, the TLR2 agonist Pam 3 CSK 4 exhibits unique immunomodulatory properties, characterized by the capacity to induce robust cytokine production by naive CD4+ T lymphocytes (both IL-10 and IFN-γ) [16][17][18][19]. In a murine asthma model, Pam 3 CSK 4 treatment improved allergic hyper-responsiveness within the airways (AHR).…”
mentioning
confidence: 99%